The Role of Pharmacists in Preventing Antibiotic Resistance: A Narrative Review - Martadiani, Kristy Rahayu; Insani, Widya Norma; Alfian, Sofa Dewi (Pharmaceutical Sciences and Research, 2026)
Antibiotic resistance is a serious global health threat, driven by irrational antibiotic use, including uncontrolled self-medication, use without proper indication, and non-adherence to medical instructions. This review aims to examine the strategic role of pharmacists in preventing antibiotic resistance through interventions at different points of healthcare services. While the discussion addresses the global pharmacist role, this review places particular emphasis on resource-limited settings, such as those in developing countries, where access to antibiotics is relatively unrestricted, regulatory enforcement is weak, and self-medication practices are more prevalent. Literature findings indicate that pharmacists play an important role as educators and supervisors of medication use, as well as partners in antimicrobial stewardship programs. In the context of self-medication, pharmacists play a key role in refusing requests for antibiotics without a prescription and in raising patient awareness. In hospital settings, clinical pharmacists are involved in validating therapeutic indications, recommending de-escalation, and ensuring adherence to evidence-based treatment guidelines. Recent studies, including those in Indonesia, have shown that active pharmacist involvement can reduce inappropriate antibiotic use and enhance patient adherence to therapy. Improved adherence significantly contributes to resistance prevention. Therefore, strengthening pharmacist capacity and regulatory support are key components in both national and global strategies to combat antimicrobial resistance.